Implementation of the Principle of Freedom of Contract in Business Agreement Law and Its Implications for Justice - Reni Ayu Anggriani; Yuni Dhea Utari; Nur Umida; Annisa Agustira (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
The principle of freedom of contract is a fundamental principle in business contract law in Indonesia which gives parties the freedom to determine the content, form and terms of the contract independently. This principle is recognized in Article 1338 of the Civil Code, which states that all agreements made legally are valid as law for the parties who make them. The implementation of this principle allows flexibility and innovation in business transactions, but remains limited by law, propriety and the public interest to prevent abuse. This research uses qualitative methods with document studies, examining various literature sources related to the principle of freedom of contract and its implications for fairness in business agreements. The research results show that the principle of freedom of contract increases efficiency and trust in business, but can also give rise to injustice if not regulated properly. Therefore, regulations and legal protection mechanisms are needed that ensure balance and justice for all parties. Upholding the principles of fairness, good faith and reasonableness in evaluating and implementing contracts is important to achieve fairness and sustainability in business relationships.